Determination of whole blood and plasma viscosity by means of flow curve analysis - Ruef, Peter; Gehm, Jutta; Gehm, Lothar; Schmidt, Claudia; Pöschl, Johannes; Kuß, Navina (General physiology and biophysics, 2014)
The LS300 viscometer permits automated measurements of viscosity at several shear rates of non-Newtonian fluids. We determined whole blood and plasma viscosity, aggregation, red blood cell deformability, and hematocrit of 66 healthy adults. The effects of the anticoagulants EDTA, heparin and citrate, and of centrifugation on blood viscosity (n=12) and red blood cell geometry (n=5) were investigated. With regard to the whole blood viscosity of adults, the best agreement was obtained by Casson's calculation compared to the methods of Ostwald, Bingham and Newton. The approximated flow curve of plasma showed only marginal differences between the method of Newton and Ostwald, whereas the latter gave the best quality of approximation. Centrifugation and the anticoagulants had a significant impact on whole blood viscosity and yield shear stress, whereas erythrocyte geometry remained unaffected. By linear regression of hematocrit with viscosity and yield shear stress, its impact on blood viscosity could be calculated in a hematocrit range of 0.32-0.50. Determination of whole blood viscosity should be performed in a standardized manner at several shear rates and without centrifugation of the blood samples.